Unlimited power : the new science of personal achievement - Robbins, Anthony (Simon & Schuster Paperbacks, 2015)
Anthony Robbins, whose seminars of transforming power havemade him an international celebrity on network television and in magazines and newspapers, shows readers how to achieve super success in all areas of their personal and professional lives. "A must for anyone committed to personal excellence".--Ken Blanchard, coauthor, "One Minute Manager."